MASJID SEBAGAI PUSAT PENDIDIKAN ISLAM PADA MASA KERAJAAN SAMPAI MASA ORDE LAMA DI BONE, SULAWESI SELATAN - Ridhwan Ridhwan; Abidin Nurdin; Wardhana Wardhana (Jurnal Ilmiah Didaktika, 2019)
Mosques as educational centers are not only found in the Middle East, but also in the Malay world this reality occurs as in Aceh, Demak, Banten and Bone. During the Kingdom of Bone until the Old Order period the mosque became the center of Islamic education in the form of recitation of the Qur'an and the Yellow Book which examined Islamic sciences such as Fiqh, Hadith, Tafsir, Akhlak, Sufism and Arabic. Kadi and Imam Masjid were the main actors who carried out the teaching spread in the Watampone region as the capital city of the Kingdom. Then it developed into other regions such as Macege, Cabalu, Palakka, Awangpone, Pattiro, Barebbo, and Cenrana. Especially in Watampone, the study was held at the Kingdom Bone Mosque, the Al-Mujahidin Mosque which was the center of Islamic education fostered by the Kadi Bone and at the Masjid Watampone Mosque which was fostered by the Imam Masjid Raya. Recitations in the Palili region of the Kingdom of Bone are generally fostered by Kadi who are both Imam and Katte (Khatib) in their respective regions. The teaching system is the same as the teaching system that generally applies in the archipelago at that time, namely the wetonan/bandongan and sorogan methods. In the Bugis tradition the Bone system is referred to as the tudang mangaji.